2014
DOI: 10.1186/1746-1596-9-115
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal Rosai-Dorfman disease involving the right atrium in a 60-year-old male

Abstract: Rosai-Dorfman disease (RDD) involving the cardiovascular system is extremely rare; to our knowledge, there are only 9 cases in the literature. Here, a case of a 60-year-old male with RDD involving the right atrium is presented. A comprehensive literature review was undertaken to summarize the clinical and pathologic features of this disorder.Virtual SlidesThe virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2143194139120169.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…RDD frequently involves extranodal sites, observed in 43% of cases. However, isolated extranodal involvement is unusual, and soft tissue involvement is even more rare [ 3 ]. Aside from a few case reports, only a few large-scale studies have assessed STRDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RDD frequently involves extranodal sites, observed in 43% of cases. However, isolated extranodal involvement is unusual, and soft tissue involvement is even more rare [ 3 ]. Aside from a few case reports, only a few large-scale studies have assessed STRDD.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnoses showing similar histologic features to RDD include inflammatory myofibroblastic tumor (IMT), Langerhans cell histiocytosis (LCH), and leukemic infiltration [ 3 ]. Some IMTs show compact spindle cell proliferation with fibrosis and diffuse inflammatory cell infiltration, similar histologic features to RDD.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnoses of a cardiac mass with microscopic features similar to those of RDD include Langerhans cell histiocytosis (in which the cells are positive for both S-100 protein and CD1a), an inflammatory myofibroblastic tumor (which has a background proliferation of spindle cells associated with an infiltrate of mononuclear inflammatory cells and ALK-1 positivity), metastatic malignant melanoma (in which cells are positive for Melan-A), Hodgkin's disease (which shows characteristic Reed-Sternberg cells and positivity for CD15 and CD30), and fungal or mycobacterial infections (which are validated by positive staining with GMS, PAS, and acid-fast stain) [ 4 ]. Literature review demonstrated three cases of right atrial involvement in RDD presenting with chest pain and hypotension or as an incidental finding, a relatively asymptomatic involvement of the left atrium as in our case has not been noted [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emperipolesis is a classic finding of DRD, characterized by numerous histiocytes that phagocytose intacts lymphocytes within their cytoplasm. The pattern of the immunohistochemical in RDD is positive for S-100, CD68 (KP-1) and CD16 protein and the absence of CD1a [7,8].…”
Section: Introductionmentioning
confidence: 99%